Peripheral and Central Mechanisms Involved in the Hormonal Control of Male and Female Reproduction. (July 2016) - Rudolph, L. M.; Bentley, G. E.; Calandra, R. S.; Paredes, A. H.; Tesone, M.; Wu, T. J.; Micevych, P. E.
Abstract : Reproduction involves the integration of hormonal signals acting across multiple systems to generate a synchronised physiological output. A critical component of reproduction is the luteinising hormone (LH) surge, which is mediated by oestradiol (E2 ) and neuroprogesterone interacting to stimulate kisspeptin release in the rostral periventricular nucleus of the third ventricle in rats. Recent evidence indicates the involvement of both classical and membrane E2 and progesterone signalling in this pathway. A metabolite of gonadotrophin‐releasing hormone (GnRH), GnRH‐(1‐5), has been shown to stimulate GnRH expression and secretion, and has a role in the regulation of lordosis. Additionally, gonadotrophin release‐inhibitory hormone (GnIH) projects to and influences the activity of GnRH neurones in birds. Stress‐induced changes in GnIH have been shown to alter breeding behaviour in birds, demonstrating another mechanism for the molecular control of reproduction. Peripherally, paracrine and autocrine actions within the gonad have been suggested as therapeutic targets for infertility in both males and females. Dysfunction of testicular prostaglandin synthesis is a possible cause of idiopathic male infertility. Indeed, local production of melatonin and corticotrophin‐releasing hormone could influence spermatogenesis via immune pathways in the gonad. In females, vascular endothelial growth factor A has been implicated in an angiogenic process that mediates development of the corpus luteum and thus fertility via the Notch signalling pathway. Age‐induced decreases in fertility involve ovarian kisspeptin and its regulation of ovarian sympathetic innervation. Finally, morphological changes in the arcuate nucleus of the hypothalamus influence female sexual receptivity in rats. The processes mediating these morphological changes have been shown to involve the rapid effects of E2 controlling synaptogenesis in this hypothalamic nucleus. In summary, this review highlights new research in these areas, focusing on recent findings concerning the molecular mechanisms involved in the central and peripheral hormonal control of reproduction.